A corpus-based longitudinal study of diction in Chinese and British news reports on Chang’e project - Rong, Lu; Xue, Xie; Jiashuang, Qi; Mohamad Ali, Afida; Jie, Zhao (Institute for Corpus Research, Incheon University Korea, 2022)
As a milestone progression in China’s space exploration history, Chang’e Project has attracted a lot of media attention since its first launching. This study aims to examine and compare the similarities and differences between the Chinese media and the British media in using nouns, verbs, and adjectives to report the Chang’e Project. After categorising the documents based on specific project phases, we created two diachronic corpora to explore the linguistic shifts and similarities and differences of diction employed by the Chinese and British media on the Chang’e Project ideology. This longitudinal study was performed with Lancsbox and the CLAWS web tagger through critical discourse analysis as the theoretical framework. The findings of the current study showed that the Chang’e Project coverage in both media increased on an annual basis, especially after 2019. In contrast to the objectivity and positivity in the Chinese Media, the British Media seemed to be more subjective with more appraisal adjectives in the news reports. Nonetheless, both countries were trying to be objective and formal in choosing nouns and verbs. Ideology-wise, the Chinese news media reports portrayed more positivity on domestic circumstances while the British counterpart was typically more critical. Notably, the study outcomes could catalyse future research on the Chang’e Project and facilitate diplomatic policies.